Electrochemically activated surface reconstruction of OER catalyst by Cr leaching - Lee, Jun Yan (Nanyang Technological University, 2020)
Global demand for energy consumption has been on the rise over the years with globalization and population growth. However, the current usage of fossil fuel as our main energy source raised concerns over the impact on our environment. Hydrogen appears to be the ideal replacement with scalable water electrolysis from renewable energy sources. However, the sluggish kinetics of oxygen evolution reaction (OER) cause it to be expansive and hindered its usage. Therefore it is important to develop an efficient OER catalyst based on first row transition metals to make water oxidation economical.